2016
DOI: 10.7475/kjan.2016.28.4.415
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Analysis for Psychosocial Variables related to Sick Role Behavioral Compliance in Hemodialysis Patients

Abstract: Purpose: This study was designed to identify the structural relationships among psychosocial variables related to sick role behavioral compliance among patients undergoing hemodialysis. Methods: The subjects were 476 patients from seven major hospitals and twelve dialysis centers located in D and P cities. Data were collected using self-report questionnaires. Data analysis was done by using SPSS/WIN 18.0 and AMOS 18.0 programs for structural equation modeling, to estimate the hypothesized model. Results: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…This finding is consistent with previous research (Moattari et al , ; Park & Lee, ) and a meta‐analysis study showed that self‐management programs were effective for the self‐efficacy of patients with chronic renal failure (Lin et al , ). Improving self‐efficacy could be an effective strategy for managing treatment compliance and interdialytic weight gain, as self‐efficacy is known to be associated with treatment compliance (Cho et al , ; Zrinyi et al , ) and interdialytic weight gain (Aliasgharpour, Shomali, Moghaddam, & Faghihzadeh, ). This study showed that the treatment compliance scores increased significantly in the experimental group after implementation of the integrated self‐management program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with previous research (Moattari et al , ; Park & Lee, ) and a meta‐analysis study showed that self‐management programs were effective for the self‐efficacy of patients with chronic renal failure (Lin et al , ). Improving self‐efficacy could be an effective strategy for managing treatment compliance and interdialytic weight gain, as self‐efficacy is known to be associated with treatment compliance (Cho et al , ; Zrinyi et al , ) and interdialytic weight gain (Aliasgharpour, Shomali, Moghaddam, & Faghihzadeh, ). This study showed that the treatment compliance scores increased significantly in the experimental group after implementation of the integrated self‐management program.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment compliance was measured by using the Compliance of Patient Role Behavior tool that had been developed for Korean hemodialysis patients. The reliability and validity of this tool have been established (Cho, Choi, & Sung, ; Lee et al , ). It measures hemodialysis patients’ compliance with dietary and water restrictions, medication, exercise, the dialysis schedule, and arteriovenous fistula management.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of other participant characteristics, self-care behavior significantly differed according to age [ 6 , 8 , 26 , 29 , 30 ], sex [ 6 , 31 , 32 ], marital status [ 6 , 8 ], economic status [ 5 ], HD-related education and social support [ 7 ], primary cause of ESRD, and occupation [ 30 ]. However, some studies [ 3 , 4 , 33 , 34 ] observed no significant differences in self-care behavior according to participant characteristics. In addition, regardless of the frequency, self-care behavior education and self-care behavior were almost the same.…”
Section: Discussionmentioning
confidence: 99%
“…이상에서 가장 낮은 것으로 나타나 [5] 이들 연령대를 중심으로 스스로 식이조절을 하고 대처능력을 증진할 수 있는 지식과 정 보를 제공할 필요가 있다 [6]. 또한 노인 혈액투석 환자는 집중 력, 기억력 같은 인지기능이 저하되어 [7], 혈액투석 식이조절 에 필요한 지식을 습득하고 유지하는 데 어려움이 있어 [6]…”
Section: 그러나 혈액투석에 대한 식이 지식이 혈액투석 환자 중 60세unclassified